From Mesoporous Silica to MOF–Silica Composites: Advancements in Nanostructured Drug Delivery Systems - Safitriono, Wahyu Nur; Saputra, Ozi Adi; Lestari, Witri Wahyu; Wibowo, Fajar Rakhman (Indonesian Journal of Chemical Analysis (IJCA), 2026)
Recent advances in nanotechnology have enabled the development of versatile drug delivery systems (DDS) using nanoscale carriers, offering significant improvements over conventional therapies. Mesoporous silica nanoparticles (MSNs) and metal–organic frameworks (MOFs) are highly porous nanomaterials with tunable structures and large surface areas, making them promising platforms for drug delivery. MSNs provide controllable particle size, pore size, and surface functionality, allowing efficient loading and controlled release of both hydrophilic and hydrophobic drugs. MOFs, with their high surface area, adjustable pore structures, and chemical versatility, enable high drug loading capacity and stimuli-responsive release. Integrating MOFs with silica to form MOF–silica composites further enhance structural stability, biocompatibility, and drug delivery efficiency. Stimuli-responsive composites can minimize premature drug release and enable targeted delivery in response to environmental triggers, such as pH or near-infrared irradiation. This review highlights the structural and functional differences among MSNs, MOFs, and MOF–silica composites, and discusses their applications in delivering model therapeutic agents, including curcumin, quercetin, and doxorubicin. The advantages, limitations, and future perspectives of these nanocarriers for precision medicine are also addressed, emphasizing their potential to improve therapeutic efficacy while reducing off-target effects.